2014
DOI: 10.2147/tcrm.s61821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacist interventions on drug-related problems and laboratory markers in outpatients with human immunodeficiency virus infection

Abstract: BackgroundSubstantial complexity has been introduced into treatment regimens for patients with human immunodeficiency virus (HIV) infection. Many drug-related problems (DRPs) are detected in these patients, such as low adherence, therapeutic inefficacy, and safety issues. We evaluated the impact of pharmacist interventions on CD4+ T-lymphocyte count, HIV viral load, and DRPs in patients with HIV infection.MethodsIn this 18-month prospective controlled study, 90 outpatients were selected by convenience sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
(40 reference statements)
1
12
0
7
Order By: Relevance
“…13 Molino et al also had similar findings in a prospective controlled study, reporting that pharmacist interventions were generally accepted by physicians, leading to a change in medication therapy. 15 Furthermore, the interventions were well accepted by patients as well, although the compliance with the interventions was not measured. 14 These findings suggest that the importance of the pharmacist in healthcare is well recognized by physicians, as is the significance of the pharmaceutical practices in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Molino et al also had similar findings in a prospective controlled study, reporting that pharmacist interventions were generally accepted by physicians, leading to a change in medication therapy. 15 Furthermore, the interventions were well accepted by patients as well, although the compliance with the interventions was not measured. 14 These findings suggest that the importance of the pharmacist in healthcare is well recognized by physicians, as is the significance of the pharmaceutical practices in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…These findings differ somewhat from those found in a previous study in which DRPs commonly involved adverse drug reactions (30.4%) and patient non-compliance (30.4%), followed by untreated indications (10.7%), drug interactions and supratherapeutic/sub-therapeutic doses (7.1% each), improper drug selection (5.4%), and drug use without indication (1.8%). 15 Another study was conducted at a private hospital in Riyadh City, Saudi Arabia to investigate the intervention of clinical pharmacist's services at critical care units. This study reported that the most common DRPs were inappropriate dose (20.05%), followed by drug duplication (11.29%), and unsuitable route (6.87%) and DDIs (1.96%).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical pharmacy team performed written and verbal pharmacist interventions with the intervention group, which were accounted for and classified as pharmacist-patient or pharmacist-physician interventions and as resolutive pharmacotherapy problems, preventive pharmacotherapy problems, quality of life, or referral to other medical specialties interventions. The classifications used for pharmacotherapy problems and pharmacist interventions are in accordance with those used in another publication by the authors [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“… 2 Partial adherence or non-adherence to ART is one of the main barriers to its effectiveness. 3 , 4 In this context, studies that identify the benefits of different pharmaceutical care practices in supporting adherence to antiretroviral therapy are necessary.…”
Section: Introductionmentioning
confidence: 99%